Integrated Waqf Farm: A Contemporary Model for Waqf Land Development - Lutfi, Alvi Amalia; Khasanah, Miftahul Nur; Agustin, Erlinda Dhika; Setiowati, Denok; Yulita, Nasywa Ayu; Medias, Fahmi (Universitas Islam Sultan Agung, 2024)
The important role of waqf is felt to have been greatly reduced recently, due to various problems faced in developing waqf land. The lack of nazhir competence, limited development capital, and management that is not yet professional are some of the many problems in waqf. Various approaches are needed to close this problem, such as changing the form of waqf, cooperation between lines, and other alternative innovations. This research aims to reveal contemporary innovation models in integrated agricultural waqf land development and analyze the benefits, opportunities, costs and risks using the analytic network process approach-Benefit, Opportunity, Cost and Risk (BOCR). This research design uses an interpretative paradigm with a qualitative approach in the form of a case study. Through content analysis, data obtained from interviews is then interpreted according to the research objectives. This research reveals that there are two types of innovation developed through the integration of agriculture in waqf development. “Bersamamu sadar ternak” is a livestock-based innovation, this innovation is the result of collaboration with farmers to produce sheep without costs being charged to partners. To strengthen the existence of tourism on this waqf land,